Potencial ameloblastomatoso del quiste dentígero en niños: reporte clinico-patológico de un caso - Villegas, Flor Angela; Aguilar, Germán; Naranjo, Rodrigo Felipe (Revista Facultad de Odontología Universidad de Antioquia, 2020)
The purpose of this report was to review the available literature and to compilate the clinical, pathological and radiological information about a case in which happened a transformation of a dentigerous cyst into an ameloblastoma. The features of both lesions were analysed for determining the veracity of the ameloblastomatous potencial of the dentigerous cyst. The possibility that the lesion had been from the beginning a misdiagnosed neoplasm, is still been discussed and the therapeutic success when given a conservative approach due to patient´s age.